Estudo do efeito do uso de parâmetros de corrente pulsada na soldagem molhada com eletrodo revestido - Orlando Mauricio Castellanos Gonzalez (2024)
The purpose of this work is to understand the use of pulsed current in underwater wet welding with a stick electrode. The wet welding technique is widely used in the offshore industry as an aid to repair work. Therefore, the study of the operational characteristics and inherent problems is of great importance to researchers in the area. In addition, the SMAW process is still the dominant technique used due to its reasonable cost, adequate weld metal quality and ease of application. In this sense, the present work includes the execution of welds with a power source that allows electronic control of the current, applying current modulation to pulsed waveform, maintaining the same average current. Depths of 0.4 m and 30 m were simulated, using direct and reverse polarity. The main results were higher average melting rates and maximum penetration of the weld bead as the effective current increased. However, a rigid arc, due to its stability at a lower current amplitude (lower average effective current value), was also able to increase the depth of penetration. In addition, a higher pulse frequency made it possible to equalize the arc voltage signal in order to improve the stability of the process.